Microscopic study of electrical properties of CrSi(2 )nanocrystals in silicon - Dózsa, László (Springer, 2011)
Semiconducting CrSi(2 )nanocrystallites (NCs) were grown by reactive deposition epitaxy of Cr onto n-type silicon and covered with a 50-nm epitaxial silicon cap. Two types of samples were investigated: in one of them, the NCs were localized near the deposition depth, and in the other they migrated near the surface. The electrical characteristics were investigated in Schottky junctions by current-voltage and capacitance-voltage measurements. Atomic force microscopy (AFM), conductive AFM and scanning probe capacitance microscopy (SCM) were applied to reveal morphology and local electrical properties. The scanning probe methods yielded specific information, and tapping-mode AFM has shown up to 13-nm-high large-area protrusions not seen in the contact-mode AFM. The electrical interaction of the vibrating scanning tip results in virtual deformation of the surface. SCM has revealed NCs deep below the surface not seen by AFM. The electrically active probe yielded significantly better spatial resolution than AFM. The conductive AFM measurements have shown that the Cr-related point defects near the surface are responsible for the leakage of the macroscopic Schottky junctions, and also that NCs near the surface are sensitive to the mechanical and electrical stress induced by the scanning probe.